1996
DOI: 10.1590/s0004-282x1996000300004
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of refractory epilepsy associated with space occupying lesions experience and review

Abstract: -Surgery for space occupying lesions of the brain associated with intractable epilepsy represents a special problem because relief of the epilepsy is as much an operative goal as excision of the space occupying lesion itself. This study concerns 32 patients with space occupying lesions and intractable epilepsy who underwent excision of the lesion with acute intraoperative electrocorticography guided resection of the epileptogenic focus. Of the 32 patients, 16 formed a subgroup of gangliogliomas alone. The rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 39 publications
0
5
0
3
Order By: Relevance
“…A small retrospective study from Brazil on 32 patients with a brain tumor and intractable epilepsy showed comparable results of neurosurgical treatment of the tumor together with the epileptogenic zone [46].…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…A small retrospective study from Brazil on 32 patients with a brain tumor and intractable epilepsy showed comparable results of neurosurgical treatment of the tumor together with the epileptogenic zone [46].…”
mentioning
confidence: 93%
“…Effect of neurosurgery on tumor-related intractable epilepsyZentner et al[43] Morris et al[44] Luyken et al[45] Brainer-Lima et al[46] …”
mentioning
confidence: 99%
“…Outros estudos com populações heterogêneas de tumor cerebral de crescimento lento também demonstraram a predominância da crise epiléptica parcial 18,19 . Award et al 20 descreveram 47 pacientes com tumor cerebral primário e epilepsia refratária, nos quais a PC não foi específica para a localização anatômica da lesão, podendo ocorrer em lesões temporais ou extra-temporais.…”
Section: Discussionunclassified
“…In addition, for intractable epilepsy associated with brain tumors, surgery may also be considered, and satisfying results with regard to seizure reduction have been reported (Brainer-Lima et al, 1996;Zentner et al, 1997;Luyken et al, 2003;Bromfield, 2004;Cascino, 2004;Paolini et al, 2006). In addition, for intractable epilepsy associated with brain tumors, surgery may also be considered, and satisfying results with regard to seizure reduction have been reported (Brainer-Lima et al, 1996;Zentner et al, 1997;Luyken et al, 2003;Bromfield, 2004;Cascino, 2004;Paolini et al, 2006).…”
Section: Surgerymentioning
confidence: 99%